The Seven Virtues of Highly Compassionate People : Tools for Cultivating a Life of Harmony and Joy. - Guerra, Nancy. (Taylor & Francis Group, 2024)
In The Seven Virtues of Highly Compassionate People, social scientists Nancy Guerra and Kirk R. Williams provide easy to follow steps to help you understand the what, the why, and the how of compassion.